Annual evolution of the prevalence of excess obesity in adults in the capitals of the 26 Brazilian states and the Federal District Between 2010 and 2019 (Research, Society and Development, 2020)
In the last two decades, Latin America has undergone an accelerated epidemiological and nutritional transition, featuring an increase in overweight and obesity, and a reduction in malnutrition, due to changes such as industrialization, urbanization, and sedentary lifestyle. Objective: to show the nutritional evolution of the Brazilian adult population through the investigation of surveys, characterizing the changes that have occurred in the last decade. Methodology: Cross-sectional study, with secondary data. The search for data came from the Surveillance System for Risk and Protection Factors for Chronic Diseases by Survey (VIGITEL). First, data analysis was carried out, which enabled the constitution of the corpus; with the analysis making it possible to reach a conclusion. Conclusion: The prevalence of morbid obesity has increased in all capitals of Brazil, with a higher percentage in the female public, in the age groups of 25 to 44 years, in all levels of education and regions of the country, an alert to the need to elaborate public health promotion policies that encourage the construction and maintenance of healthy lifestyles even in childhood and adolescence. Because obesity is a condition that can facilitate the emergence of chronic non-communicable diseases, such as cardiovascular disease, cancer, diabetes mellitus and high blood pressure.